1990
DOI: 10.3109/01913129009076133
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical Ultrastructural Pattern in Fabry's Disease: A Study on Its Nature and Incidence in 7 Cases

Abstract: This is a report on a stored lipid atypical ultrastructural pattern in skin samples of Fabry's disease expressed exclusively in the endothelium. The pattern consisted of intersecting short crescentic tightly packed membranes with a periodicity identical to that in classical ultrastructural variants. At low magnification the lysosomal aggregates of the material resembled "sunbursts" or aggregates of densely packed squirming villus-like structures. According to results of ultrastructural, lipid, and lectin histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Previous studies characterizing the accumulated glycosphingolipids in Fabry disease used biochemical, histochemical and immunohistochemical techniques 8–10 . However, biochemical and histochemical methods present considerable difficulties because some of the solvents employed in the experimental procedures extract lipid‐laden materials 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies characterizing the accumulated glycosphingolipids in Fabry disease used biochemical, histochemical and immunohistochemical techniques 8–10 . However, biochemical and histochemical methods present considerable difficulties because some of the solvents employed in the experimental procedures extract lipid‐laden materials 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies characterizing the accumulated glycosphingolipids in Fabry disease used biochemical, histochemical and immunohistochemical techniques. [8][9][10] However, biochemical and histochemical methods present considerable difficulties because some of the solvents employed in the experimental procedures extract lipid-laden materials. 11 Electron microscopy studies demonstrated the fine structure of these deposits; 12 however, the use of osmium tetroxide, a strong oxidizing agent for lipid fixation, greatly restricts the usefulness of electron microscopy histochemical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…On semithin sections, GL deposits appear as a deep blue-stained intracellular bodies [8,9]. TEM analysis show the fine structure of Fabry lipids, characterized by densely packed lamellas, arranged in onion-like, zebra-like, or filament-like figures [10,11].…”
mentioning
confidence: 99%
“…It is possible that there is already extensive storage of CTH early in life or even prenatally, while symptoms develop much later. To the best of our knowledge, manifestations of Fabry disease in placental tissue have been reported only twice (Elleder et al 1998;Popli et al 1990). In the first case report, Popli and colleagues describe a placenta of a heterozygous mother who carried a healthy child.…”
mentioning
confidence: 99%
“…The fetal portion of the placenta was reported to be free of storage material. Early storage in the fetal part of the placenta has been described for a male Fabry fetus (Elleder et al 1998), but relationship with genetic abnormalities, residual enzyme activity and biochemical measures of storage has so far not been reported.…”
mentioning
confidence: 99%